2023
DOI: 10.2337/dc22-1359
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Dietary Iron Intake and Genetically Determined Iron Overload: Risk of Islet Autoimmunity and Progression to Type 1 Diabetes in the TEDDY Study

Abstract: OBJECTIVE To examine whether iron intake and genetically determined iron overload interact in predisposing to the development of childhood islet autoimmunity (IA) and type 1 diabetes (T1D). RESEARCH DESIGN AND METHODS In The Environmental Determinants of Diabetes in the Young (TEDDY) study, 7,770 genetically high-risk children were followed from birth until the development of IA and progression to T1D. Exposures included ener… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Recent studies show conflicting results regarding iron intake and the risk of developing T1D in children; One study suggested that high iron intake was associated with an increased risk of islet autoimmunity in children with high genetic risk of T1D (80). Another study showed that higher iron intake at the time of islet autoimmunity was associated with a lower risk of progression to T1D (81).…”
Section: Iron and Risk Of Diabetesmentioning
confidence: 99%
“…Recent studies show conflicting results regarding iron intake and the risk of developing T1D in children; One study suggested that high iron intake was associated with an increased risk of islet autoimmunity in children with high genetic risk of T1D (80). Another study showed that higher iron intake at the time of islet autoimmunity was associated with a lower risk of progression to T1D (81).…”
Section: Iron and Risk Of Diabetesmentioning
confidence: 99%